Key indicators of obstetric and neonatal care in the Republic of Sakha (Yakutia). Issue 1 (1st January 2016) - Burtseva, Tatyana E.; Odland, Jon Øyvind; Douglas, Natalya I.; Grigoreva, Antonina N.; Pavlova, Tatyana Y.; Chichahov, Dgulustan A.; Afanasieva, Lena N.; Baisheva, Nurguyana S.; Rad, Yana G.; Tomsky, Mikhail I.; Postoev, Vitaly A.
Abstract : In the absence of a medical birth registry, the official statistics are the only sources of information about pregnancy outcomes in the Republic of Sakha (Yakutia) (RS). We analysed the official statistical data about birth rate, fertility, infant and maternal mortality in the RS in the period 2003–2014. Compared with all-Russian data, the RS had a higher birth rate, especially in rural districts. Maternal and infant mortality were also higher compared with all-Russian data, but had a decreasing trend. The majority of deaths occurred in the small level 1 units. We suggest that establishment of good predelivery transportation of pregnant women with high risk of complications from remote areas and centralization of risk deliveries with improved prenatal and neonatal care could improve the pregnancy outcome in Yakutia.